Pengaruh Lingkungan Kerja, Motivasi dan Efikasi Diri Terhadap Kinerja Karyawan Pada CV. Pesona Sakti Bangkalan Di Masa Pandemi Covid-19 - Abd. Rosid; S Anugrahini Irawati (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
CV. Pesona Sakti is a company in construction services. It has a very tight competition, CV. Pesona Sakti has had commitment and powerd by improving the employees performance. This study analyzes the effect of the work environment, motivation, and selfefficacy on employees performance during the covid-19 pandemic. The independent variables are work environment, motivation and self-efficacy and the dependent variable is employees performance. The data collection method uses a questionnaires and the data analyzes using multiple linear regression. The results indicate that the work environment has a  positive and significant effect on the employees performance with a value is 2.517 and the significance value is 0.015 0.05. Motivation has a positive and significant effect on the employees performance with a value is 4.120 and the significance value ois 0.000 0.05. Self-efficacy has a positive and significant effect on employees performance with a value is 2.109 and the significance value is 0.040 0.05. Simultaneously, the work environment, motivation, and self-efficacy have a positive and significant effect on the employees performance with a value is 44,4692.81 and the significance value is 0.0000.05.